Avoidable Cost: Ride a Double Auction Roller Coaster - Boening, Mark Van; Wilcox, Nathaniel T. (American Economic Review, 1996)
The double auction trading institution has been highly efficient across diverse marginal-cost market structures, whether human subjects or 'zero-intelligence' robots populated those markets. Accordingly, many researchers suspect that double auction performance transcends market structure and agent strategy. But the authors show that large avoidable costs undermine the efficiency and stability of human subject double auctions and these low human efficiencies are simultaneously well above zero-intelligence efficiencies. Their results dramatically illustrate the potential havoc wrought by highly competitive institutions when they must cope with nonconvex technologies. Copyright 1996 by American Economic Association.